Breastfeeding practices and social support among mothers in District V, Manila - Tubera, Sophia A.; Rosal, Melvin Joseph D.; Stephanson, Zoe O.; Tabungar, Kaezzy Ila B.; Turingan, Angelo Joseph; Uy, Kathleen Nicole T.; Vibieda, Jade Louise L.; Villanueva, Mary Grace B. (Manila College of Nursing University of the Philippines, 2018)
In the Philippines, exclusive breastfeeding (EBF) remains stagnant with only half
of all the neonates being exclusively breastfed (Philippine Statistics Authority, 2013).
Social support is one key indicator of a mother’s decision to initiate and continue
breastfeeding and has been found to have direct positive outcomes on breastfeeding rates.
This research aims to: (1) describe current breastfeeding practices of mothers with young
infants; (2) determine knowledge of mothers on breastfeeding; (3) determine the level of
social support that mothers receive; (4) determine factors affecting current practice in
terms of breastfeeding knowledge and social support; (5) determine factors affecting
intention to continue breastfeeding in terms of current practice and social support.

This study is descriptive correlational in nature. Purposive sampling was used and
inclusion criteria were: (1) women 18 to 50 years, with infants 1-6 months old who
breastfed the infant, and (2) husbands or other family members of mother respondents, 18
years of age or older. The study was done at 5 selected health centers in District V,
Manila. Self-administered questionnaire adapted from several breastfeeding tools was
utilized to gather data. The target sample size was reached with a total of 205 mothers, 66
husbands, and 42 other family members who participated in the study. Spearman Rho
correlation test, Mann-Whitney U test, and Kruskal Wallis H tests were utilized to
analyze relationships of variables.

Results of the study showed that EBF rates (32%) are still low and not at par with
WHO target of increasing exclusive breastfeeding among infants younger than 6 months
to 50% by the year 2025. Result was consistent with the global EBF rate of only 36% in
2007-2014. The practice of breastfeeding can be associated with different factors that can
affect the mother’s ability to breastfeed. Knowledge of mothers on breastfeeding was
found to be suboptimal. Social support was found to be high for all mothers, with highest
reported support from the health care providers. However, among the three sources of
support, only with the husbands was there enough evidence to suggest a relationship
between current breastfeeding practices and social support. Despite the high social
support provided by the husbands, there were more mothers who did not practice
exclusive breastfeeding, which may be attributed to negative support. Social support was
also found to influence maternal intention to breastfeed exclusively for six months and
continue breastfeeding up to 2 years. Since support has been shown to have a relationship
with breastfeeding practice and intention, active involvement of husbands and other
family members in the breastfeeding interventions during the antenatal and postnatal
period should be encouraged to help correct misconceptions and promote appropriate and
adequate breastfeeding support.
Accomplishment report (In partial fulfillment of the requirements for the course N121.2: Intensive Nursing Experience) -- University of the Philippines Manila, June 2018.
Keywords: Intensive community experience